Teleconnections between the Peruvian central Andes and northeast Brazil during extreme rainfall events in austral summer - Sulca Jota, Juan Carlos (2016)
Extreme precipitation events in the Peruvian Andes have significant socioeconomic impacts, yet their atmospheric dynamics are poorly understood. Here austral summer (December–March) wet and dry spells and their continental- and large-scale teleconnections are analyzed using reanalysis, gridded, and in situ precipitation data. Dry and wet spells in the Peruvian Andes show a pervasive dipole pattern with precipitation anomalies of the opposite sign over northeastern Brazil. Composite anomalies of various atmospheric fields during extreme precipitation events indicate that this dipole is related to large-scale adjustments in the upper-tropospheric Bolivian high–Nordeste low system, which in turn are modulated by northward-propagating extratropical Rossby wave trains. At upper- and midtropospheric levels, westerly wind anomalies over the Peruvian Andes suppress moisture flux from the Amazon during dry events, while wet events are characterized by opposite conditions. Yet, while easterly wind anomalies appear to be a prerequisite for heavy precipitation events in the region, they are not a sufficient forcing, as dry days can still occur during such periods. Dry spells in the Peruvian Andes appear to be linked to weakened convective activity over the western tropical Pacific, consistent with the previously documented El Niño influence over the region. Extreme dry and wet spells in northeastern Brazil only show a weak link to precipitation anomalies of the opposite sign over Peru but are strongly coupled with changes in the position and strength of the Nordeste low and the South Atlantic convergence zone.